N-Heterocyclic carbene-catalyzed synthesis of alpha-trifluoromethyl esters - Gelat, Fabien; Patra, Atanu; Pannecoucke, Xavier; Biju, Akkattu T.; Poisson, Thomas; Besset, Tatiana (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed trifluoromethylation of alpha-chloro aldehydes was developed, allowing straightforward access to valuable alpha-trifluoromethyl ester derivatives. The unique combination of an electrophilic trifluoromethylation reagent with NHC catalysis was the key for the functionalization of a broad range of alpha-chloro aldehydes, and the products are formed in moderate to good yields. Investigations of the enantioselective version of this reaction afforded the enantioenriched products in moderate yields with good ee values.

Synthesis of 4-difluoromethylquinolines by NHC-catalyzed umpolung of imines - Patra, Atanu (Organic Letters, 2018)
The N-heterocyclic carbene (NHC)-catalyzed umpolung of aldimines for the synthesis of 4-difluoromethylquinoline derivatives is reported. In the presence of NHCs, the intramolecular cyclization of aldimines bearing a moderately electron-poor double bond due to the presence of the −CF3 group likely proceeds via the intermediacy of the aza-Breslow intermediate. The key to the success of this aza-Stetter type transformation is the NHC generated from the bicyclic triazolium salt using DBU as the base.